Portable and Rapid Smartphone-Based Colorimetric Assay of Peracetic Acid for Point-of-Use Medical/Pharmaceutical Disinfectant Preparation - Suphakorn Katib; Sutasinee Apichai; Jutamas Jiaranaikulwanitch; Busaban Sirithunyalug; Fumihiko Ogata; Naohito Kawasaki; Kate Grudpan; Chalermpong Saenjum (Molecules)
A simple and rapid smartphone-based colorimetric assay for peracetic acid concentration was developed to facilitate point-of-use disinfectant preparations for infection prevention and control. The colorimetric detection was based on the oxidation of N,N-diethyl-phenylenediamine by peracetic acid through an intermediate reaction with potassium iodide, resulting in pink-magenta products. The colorimetric reaction was performed on a 96-well plate; then, the color products were photographed in one image. The color intensity was evaluated to determine the peracetic acid concentration using a custom-built mobile application named Modern Peracetic Acid Analysis. The relative green intensity of the pink-magenta products was directly proportional to the peracetic acid concentration in the range of 0.15 to 3.0 µg/mL. The detection and quantitation limits were 0.11 µg/mL and 0.34 µg/mL, respectively. The approach was successfully applied to determine the peracetic acid concentration in pharmaceutical disinfectant formulations. The results obtained using the proposed approach showed no significant differences from those obtained using acid–base titration at the 95% confidence level. The greenness of the proposed approach was evaluated using the Complementary Green Analytical Procedure Index, Analytical Greenness, and Blue Applicability Grade Index, demonstrating enhanced environmental friendliness and practical advantages, as well as simple, portable instrumentation that is easier to operate than traditional spectrophotometric and titration methods. Furthermore, a sustainability assessment based on the Need, Quality, and Sustainability index underscored its enhanced sustainability.